The Effects of Passive and Active Smoking on Brachial and radial Blood Pressure and Some Other Physical Factors in Healthy Young Adults - Ramadhan, Shireen H.; Talal, Shamil K.; Moner, Wasfiya A. (Science Journal of University of Zakho, 2017)
Tobacco smoke is enormously harmful to human health, thereâ€™s no safe way to smoke. The primary objective of this study is to analyze the role of tobacco smoke compounds and their ability to damage the cardiovascular system and, in particular, to interfere with blood pressure (Brachial and radial pressure), heart rate and partly on the percentage blood Oxygen saturation. A new device has been manufactured which is unique for measuring the level of smoke, to obtained privies readings, the device had fixed to the first reference level آ and starting up from it. The effect of smoking has been studied on (26) male passive (26) active smoker volunteer, (14) female passive and (14) female active smoker participants. The results has been showed that the blood pressure and heart rate has been increased with increasing the number of cigarettes in both genders for passive and active smokers. However, this effect for male was more pronounced comparing with females for passive and active smokers. In the case of oxygen saturation concentration percentage, for males the change of oxygen concentration percentage was not stable. In other words, it was fluctuated with the number of cigarettes. But for females the oxygen concentration was decreased but not too much. This means that this effect was not pronounced. this study found آ that the most pronounced effect has been shown by maleâ€™s comparison to females for both passive and active smokers. As well as in nonsmokerâ€™s males, the relation between heart rate and smoke level is inversely proportional. While in male and female smokers and female nonsmokers the relation is proportional. In all cases the relation between the smoke level and time of smoking is inversely proportional. Finally males& females are affected differently by tobacco use; the sensitivities to smoke for males are higher than in females for passive and active smokers in both brachial and radial blood pressure measurement.